Embedded multimedia gateway for smart home environment - Perumal, Thinagaran; Ramli, Abd Rahman; Chui, Yew Leong; Shafie @ Musa, Siti Mariam; Mansor, Yaakob (2005)
In this paper, a new scheme in smart home systems technology is proposed using embedded multimedia gateway to provide intelligent control of home appliances. The proposed gateway has an embedded module needed to act as protocol glue that incorporates wireless options such as Short Message Service (SMS) router with wireless local area network (WI-FI) for intelligent automation and higher speed of home appliances connectivity. Wireless fidelity technology (WI-FI) is selected as mechanism due to its transmission range within 100m which suits the smart home requirement for automation and control thus justifies the Personal Area Network (PAN) for mobile device connectivity. This interface model will be between in-home-networks and external communication environment, whereas embedded multimedia gateway module acts as storage media for information interchange and server between systems using mobile devices within a smart home. Embedded multimedia gateway module sits at the core of the home network, acts as residential gateway and enables bi-directional communication and data transfer channel among networked appliances in the home and across the Internet. The proposed embedded multimedia gateway had been implemented and verified that the system can be a core device for smart home environment functionality.